PENGEMBANGAN MODUL PEMBELAJARAN ILMU EKONOMI BERBASIS TECHNOPRENEURSHIP DI UNIVERSITAS NEGERI GORONTALO - Herwin Mopangga (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
This research aims to know how about the level of students understanding and masteringof economics, and to develop learning module of economics based on technopreneurship. Used descriptive and qualitative approach where the process preceded by observation and identification learning of economics and entrepreneurship applied in 15 program undergraduate studies and a diploma in State University of Gorontalo (UNG). Data collection by documentation, literature study and questioner to 100purposive students.Research concluded that 1) students aware that the importance to understand and analysedof the development of economics not only for the benefit of academic but also to create of new jobs, 2 ) the results of economics learning 2014/2015 in UNGshows quite satisfactory based on percent comparison stayed on course for a value of A, B and C each 36, 50 and 14 percent, 3)learning more attractive and right on target, need to enriched with learning module of economics that are contextual and applicative.Module has help students to understand social reality as an unemployment intellectual and the importance of improving activities on innovative entrepreneurial.For local people in Gorontalo especially UNG, technopreneurship is well known relatively new even foreign to some students.There should be deepening and expansion of research and development activities to values technopreneurship who aims for increasing the quality of human resources and those competitivenessto face the implementation of ASEAN Economic Community 2016.